Exercise-based strategies to prevent muscle injury in elite footballers: a systematic review and best evidence synthesis - Fanchini, M.; Steendahl, I. B.; Impellizzeri, F. M.; Pruna, R.; Dupont, G.; Coutts, A. J.; Meyer, T.; McCall, A. (Sports Medicine, 2020)
Background: Exercise-based strategies are used to prevent muscle injuries in football and studies on different competitive-level populations may provide different results. Objectives: To evaluate the effectiveness of exercise-based muscle injury prevention strategies in adult elite football. Methods: A systematic search was conducted in PubMed (MEDLINE), Web of Science, Cochrane Library, and SPORTDiscuss (EBSCO). We considered only elite adult (> 16 year-old) football players with no distinction for gender; the intervention to be any exercise/s performed with the target to prevent lower-limb muscle injuries; the comparison to be no injury prevention exercise undertaken; the outcome to be the number of injuries, injury incidence, and severity. We searched systematic reviews, randomized-controlled trials (RCTs), and non-randomized-controlled trials (NRCTs), limited for English language. Risk of bias was assessed using the Risk of Bias in Systematic Reviews tool, the Cochrane Collaboration`s Tool for assessing risk of bias in RCTs, and the Risk of Bias in NRCTs of Interventions tool. Results: 15 studies were included. Three systematic reviews showed inconsistent results, with one supporting (high risk of bias) and two showing insufficient evidence (low risk of bias) to support exercise-based strategies to prevent muscle injuries in elite players. Five RCTs and seven NRCTs support eccentric exercise, proprioception exercises, and a multi-dimensional component to an injury prevention program; however, all were deemed to be at high/critical risk of bias. Only one RCT was found at low risk of bias and supported eccentric exercise for preventing groin problems. Conclusion: We found limited scientific evidence to support exercise-based strategies to prevent muscle injury in elite footballers.